Issues in Teaching Speaking Online (The Explora, 2020)
Online education changes all components of language teaching and learning, particularly in teaching speaking. Online speaking class are usually recorded so both teachers and students can go back and watch and listen to the interaction again. This is beneficial for feedback, consolidation and correction, something that doesn’t usually happen in face-to-face classrooms. However, despite the rapid growth of technology in education, some issues arise concerning with the usedigital platform in teaching English. A review of literature using Cooper’s framework was conducted to identify such issues. Two major categories of findings were identified: issues related to online learners included learners’ readiness and participation in online class, while instructors’ issue related to transitioning from face-to-face to online, time management, and teaching styles.